Investigation of ignition process from visible to infrared by a high speed colour camera. (1st December 2016) - Wang, Y.; Zheng, L.; Woolley, R.; Zhang, Y.
Highlights: Selective image processing is used to enhance the weak blue and infrared signals. Flame emission from visible to infrared spectrum is simultaneous visualised. The infrared emission is found to be associated with the soot formation process. The infrared emission only soot is in between blue flame and the visible soot. Abstract: From the image processing of high speed colour images of flame ignition, areas of dominant infrared emission have been noticed, which has stimulated the more in depth investigation in this paper. Two test cases for propane and methane with co-flow air were carried out. By applying selective digital image enhancement technique, the weak chemiluminescence-induced visible flame and infrared signals are simultaneously resolved together with the much stronger visible soot radiation. It is found that the pockets of soot only emitting infrared signal exists in both propane and methane ignition process cases. In the ignition process, the chemiluminescence-induced blue flame is observed first, which is followed by soot only having infrared emission. The visible orange coloured sooty flame only appears afterwards. The soot only emitting infrared is found in between the blue flame and the visible sooty flame. The co-flow air is found to accelerate the ignition process and it also brings forward soot formation. The investigation demonstrates that a proper image enhancement technique is essential in the further understanding of combustion process taking place when using a high speed camera.